Confocal scanning optical microscopy and related imaging systems - Corle, Timothy R.
This book provides a comprehensive introduction to the field of scanning optical microscopy for scientists and engineers. The book concentrates mainly on two instruments: the Confocal Scanning Optical Microscope (CSOM), and the Optical Interference Microscope (OIM). A comprehensive discussion of the theory and design of the Near-Field Scanning Optical Microscope (NSOM) is also given. The text discusses the practical aspects of building a confocal scanning optical microscope or optical interference microscope, and the applications of these microscopes to phase imaging, biological imaging, and s.